Analisis Deskriptif Authentic Atmospherics - Ridwanudin, Oce; Dewi, Tita Rostika (THE Journal : Tourism and Hospitality Essentials Journal, 2018)
The number of guests who make purchases at the Sapulidi Resto, Resort Restaurant, and Gallery, a themed restaurant in Bandung, does not match the targets set by the management. The management has established authentic atmospherics scape to stimulate guests who come and make purchases. This study aims to obtain findings on the description of authentic atmospherics space implemented in the restaurant. The type of research used is descriptive analysis with the method used is explanatory survey and cross sectional technique. A total of 100 guests at the restaurant became the unit of analysis of this research. The result of data processing showed that the music dimension got the highest value while the furnishing dimension got the lowest value.